2013
DOI: 10.1002/hyp.9670
|View full text |Cite
|
Sign up to set email alerts
|

Lake/watershed sulfur budgets and their response to decreases in atmospheric sulfur deposition: watershed and climate controls

Abstract: Abstract:Atmospheric sulfur (S) emissions peaked in North America in the early 1970s followed by declines in S deposition and sulfate (SO 4 2À ) concentrations in surface waters. Changes in S biogeochemistry affect the mobilization of toxic (Al +3 , H + ) and nutrient (Ca 2+ , Mg 2+ , K + ) cations, and the acid-base status of ecosystems. We focused on lake/watersheds in the Adirondack Mountains of New York, USA, one of the most acid-sensitive and acid-impacted regions in North America. We used 16 of the 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Also shown are ANC targets of 11 meq L À1 and 20 meq L À1 . till watersheds, because thin till watersheds have less capacity to neutralize and retain SO 4 2À , therefore atmospheric SO 4 2À deposition is largely transported to surface waters (Mitchell et al, 2013). Moreover, since medium or thick till watersheds exhibit greater supply of acid neutralizing base cations and retain atmospheric inputs of SO 4 2À and NO 3 À lakes adjacent to these watersheds experienced less severe historical acidification in response to elevated acid deposition and will recover more slowly compared to lakes with thin till watersheds.…”
Section: Estimated Tmdlmentioning
confidence: 99%
“…Also shown are ANC targets of 11 meq L À1 and 20 meq L À1 . till watersheds, because thin till watersheds have less capacity to neutralize and retain SO 4 2À , therefore atmospheric SO 4 2À deposition is largely transported to surface waters (Mitchell et al, 2013). Moreover, since medium or thick till watersheds exhibit greater supply of acid neutralizing base cations and retain atmospheric inputs of SO 4 2À and NO 3 À lakes adjacent to these watersheds experienced less severe historical acidification in response to elevated acid deposition and will recover more slowly compared to lakes with thin till watersheds.…”
Section: Estimated Tmdlmentioning
confidence: 99%
“…6). Other research has also found that the basal area of acid-tolerant tree species was inversely correlated with nitrification rates due to leaf litter nutrient concentrations and associated C : N ratios (Christ et al, 2002;Finzi et al, 1998;Mitchell et al, 2003;Ross et al, 2009). Within the upper elevations of Grass Pond subwatershed 5 where black cherry groves were identified, fresh black bear scat loaded with black cherry seeds was observed during early October field sampling, indicating a bear den in the area.…”
Section: Discussionmentioning
confidence: 90%
“…The associations between sugar maple basal area and high stream water high ANC and low stream water DOC indicates deep sub-surface hydrological flow paths through thick mineral soil layers and parent material (Fig. 6) (Chen et al, 1984;Mitchell et al, 2013;Driscoll and Peters, 1987). In general, sites with thick soil layers with relatively high soil pH and Ca concentrations are more likely to be colonized by sugar maple trees than other less suitable more acidic sites because of the relatively high nutrient demands of this tree species (Bailey et al, 2004;Burns and Honkala, 1990;Christopher et al, 2006;Van Breemen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enhanced NO 3 -leaching has been reported in forested watersheds exposed to chronic atmospheric N deposition, suggesting an excess of N in these ecosystems (e.g., Aber 1992;Fenn et al 1998). SO 4 2-leaching might be accelerated by the mobilization of the S that has accumulated in the soil for the past several decades (Mitchell et al 2013). Surface water acidification via leaching of strong acids affects aquatic organisms, whose distributions vary widely according to their sensitivities to acidification (Schindler 1988).…”
Section: Introductionmentioning
confidence: 97%